Mucocele in a 35-year-old patient - a case report - Chiżyński, Adam; Stelmach, Rafał; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2017)
The article describes a case of an oral mucocele of the tongue treated with a carbon dioxide laser.